Pembinaan Shalat Sesuai Himpunan Putusan Tarjih Muhammadiyah di Desa Kaliwadas, Kecamatan Bumiayu, Kabupaten Brebes: Guidance on Prayer According to the Muhammadiyah Tarjih Decision Collection in Kaliwadas Village, Bumiayu District, Brebes Regency - Muamar, Muhamad; Pratama, Havidz Cahya; Basuki, Samudra Prihatin Hendra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Muhammadiyah Branch Leadership (PRM) Kaliwadas, Bumiayu, Brebes, has experienced developments in preaching and religious activities. This is demonstrated through routine activities, such as religious studies every Wednesday night and Aisyiyah religious studies every Friday afternoon. However, there are still obstacles in the dissemination of information and understanding of the products of the fatwa thoughts of the Tarjih and Tajdid Council of the Muhammadiyah Central Leadership. This condition has an impact on the lack of understanding and practice of prayer worship by the Muhammadiyah manhaj among residents affiliated with the organization. Therefore, through Community Service activities, the implementation team in collaboration with the PRM Kaliwadas management held training on how to pray based on the Tarjih Decisions Association (HPT). The implementation of this activity involved a series of counseling sessions, direct practice, and interactive discussions to improve participants' understanding and skills in performing prayers according to Muhammadiyah's guidance. The results of the activity showed an increase in participants' understanding of the principles of Muhammadiyah fiqh, including aspects of pillars, sunnah, and things that invalidate prayer. In addition, there is an increase in awareness of implementing the tarjih method in everyday life, which is reflected in the enthusiasm of participants in discussing fiqh issues more critically. Thus, this activity can contribute to improving the quality of individual worship and strengthening the tarjih tradition in the PRM Kaliwadas environment as part of an effort to build understanding and practice of Islamic teachings by the principles of Muhammadiyah.